Optimization of cultivation conditions of Bacillus genus bacteria for proteolytic enzymes production - Barska, Ie. G. (Problems of Environmental Biotechnology, 2014)
The spectrum of economically viable protein substrates that can be used in production of proteolytic enzymes was determined. Based on the experimental data component’s composition of the nutrient medium was optimized. The maximum proteolytic activity of the genus Bacillus bacteria was determined in the case of their incubation for 72 hours at temperature 37 °C on a medium with concentrations of wheat bran protein – 1,42 % and wheat flour protein – 1,58 %.